1999
DOI: 10.1111/j.1439-0434.1999.tb03834.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Pythium ultimum by Biowaste Composts in Relation to Compost Microbial Biomass, Activity and Content of Phenolic Compounds

Abstract: Seventeen composts from separately collected organic household waste plus one bark compost and one compost from grape marc were analysed for suppression of Pythium ultimum\ phytotoxicity\ microbial biomass and activity\ substrate!induced respiration\ extractible phe! nolic compounds and other physical and chemical par! ameters[ Nine of the samples were mildly suppressive to P[ ultimum\ the others were conducive[ The bark compost sample was strongly suppressive[ Therefore of the exam! ined composts\ only the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…Several studies have reported tight correlations between the natural suppressive capacity of the soil, the level of microbial populations, and the OM content (Erhart et al, 1999; According to a previous report (Abawi and Widmer, 2000), wastewater used for irrigation can also affect the microbial diversity in the soil, including the relationships among the different species in terms of suppression of plant pathogens such as F. oxysporum, which is responsible for plant vascular diseases.…”
Section: Microbiological Analysis and Productive Characteristics Of Tmentioning
confidence: 99%
“…Several studies have reported tight correlations between the natural suppressive capacity of the soil, the level of microbial populations, and the OM content (Erhart et al, 1999; According to a previous report (Abawi and Widmer, 2000), wastewater used for irrigation can also affect the microbial diversity in the soil, including the relationships among the different species in terms of suppression of plant pathogens such as F. oxysporum, which is responsible for plant vascular diseases.…”
Section: Microbiological Analysis and Productive Characteristics Of Tmentioning
confidence: 99%
“…To date, compost amendment has been successfully used to increase soil suppressiveness to diseases in agricultural crops, including nematode diseases (Erhart et al 1999;Lumsden et al 1983;Oyarzun et al 1998;Serra-Wittling et al 1996;Steinberg et al 2004;Widmer et al 2002), as well as disease suppression in horticultural crops (Cotxarrera et al 2002;Hoitink and Boehm 1999). The mechanisms involved, however, are not fully understood yet and subject of ongoing studies.…”
Section: Organic Amendmentsmentioning
confidence: 99%
“…Many authors have correlated the suppression of certain plant diseases with organic parameters related to physicochemical properties (28,29), microbial biomass (30,31), microbial diversity (23,32), microbial community composition (33,34), microbial overall activity (30,35), metabolic and enzymatic profiles (34,36), and particular enzymatic activities (37,38). Even if certain of these parameters are better predictors than others, none is universally related to disease suppression, and their correlation with suppressiveness is largely dependent on the pathosystem, the type of amendment used, and the environmental conditions (26,27).…”
mentioning
confidence: 99%